Indigenous Knowledge and Contested Spirituality in Canadian Nuclear Waste Management - Weatherdon, Meaghan Sarah (Journal for the Study of Religion, Nature and Culture, 2017)
Indigenous spirituality is often deployed in grassroots environmental movements as a strategy to revitalize cultures and contest a hegemonic worldview that continues to marginalize Indigenous Peoples. From this perspective, Indigenous spirituality serves as an epistemological foil that these social movements utilize to critique prevailing capitalist values, environmental degradation, and neo-colonialism. Indigenous spiritual knowledge is also being employed by government and industry as a strategy to enhance the prolle of their own political and commercial agendas. Indigenous spirituality has therefore come to signify a wide variety of meanings and concerns in environmental management and public discourse. This can be illustrated by considering how Indigenous spirituality has become a site of contestation between the Nuclear Waste Management Organization (NWMO), the public body responsible for managing Canada’s used nuclear fuel, and the Committee for Future Generations (CFFG), a grass roots anti-nuclear organization, regarding the proposal to store nuclear waste in Northern Saskatchewan.